Pattern of Cleft Lip and Palate According to Gender in Children of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Cleft defects are the most common congenital anomalies of the orofacial region. The typical distribution of cleft type is cleft lip, cleft palate and combined cleft lip and palate. To determine the frequency of Cleft Lip (CL), Cleft Palate (CP) and combined cleft lip and palate (CLP) according to gender. Materials and methods: It is a cross sectional observational study with some analytical components which was carried out in the Department of Anatomy of Chittagong Medical College From April 2021 to March 2022. It was conducted among 100 children of cleft lip and palate. Data was collected from LMRF (Lions Mukhlesur Rahman Foundation) Children Hospital, Smile train (CMSOGH) cleft project and Chattogram Maa Shishu O General Hospital, Agrabad Chattogram. The data were recorded in a predesigned questionnaire. Variables were presented as percentages (%) and were compared by Chi-Square test. All statistical analysis were performed using SPSS statistics for Windows, version 26.0. Finally the results were presented using tables and figures. Results: Among the 100 participants there were 58 male and 42 female children with a ratio of 1.38:1. 68% had combined cleft lip and palate, 22% had isolated cleft palate and only 10% had isolated cleft lip. Among the 10 children with cleft lip 4 were male and 6 were female. 80% of the cleft lip was on the left side. Among 22 children of cleft palate 9 were male and 13 were female. Lastly among 68 children of cleft lip and palate 45 were male and only 23 were female. 44% of cleft lip and palate was on the left side, 32% bilateral and only 24% was on the right side. Conclusion: This study reported the pattern of cleft defects with gender distribution in our country which shows females are more likely to have isolated CL and CP and males have CLP predominantly.Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 3-7